Coronary perforation after intravascular lithotripsy for severe stent underexpansion in a heavily calcified lesion. Issue 1 (10th August 2021) - del Val, David; Rivero, Fernando; Cuesta, Javier; Bastante, Teresa; Alfonso, Fernando
Abstract : Supplemental Digital Content is available in the text.